ANATOMIC AND MORPHOLOGICAL SIGNS OF A DIFFUSE-GENERALIZED HYPERTROPHIC CARDIOMYOPATHY - S. L. Dzemeshkevich; Yu. V. Frolova; S. Yu. Kim; D. N. Fedorov; E. V. Zaklyazminskaya; S. V. Fedulova; A. N. Shapiyeva; M. S. Malikova; A. N. Lugovoy (Российский кардиологический журнал, 2015)
Aim. Based on the instrumental, histological and genetic studies to show the role and significance of intracardial anomalies and morphological specifics of the special form of hypertrophic cardiomyopathy (HCM), that the authors name as diffuse-generalized. Material and methods. A clinical, instrumental, histological and molecular-genetic study was conducted with 16 enrolled patients with diffuse-generalized form of HCM, who underwent complex surgical interventions: by transaortal approach the extended myoectomy of interventricular sept, and by intraatrial approach — parietal resection of papillary muscles, and universal chordal-sparing mitral valve replacement.Results. There was no in-hospital mortality. The long-term results for up to 5 years show that all patients moved from the IV-III NYHA to I-II NYHA functional classes. Morphological study showed that in the base of myocardial mass increase in HCM there is neither hypertrophy, but hyperplasia of cardiomyocytes. All 16 patients showed significant signs of myxomatous mitral valve degeneration.Conclusion. Diffuse-generalized type of HCM is due to spread hyperplasia process in myocardium. The invented radical remodeling operation abolishes intraventricular severe changes of pressure and increases diastolic volume of the left ventricle, preventing diastolic dysfunction development.